Methodology and Participation for 2020 Diary Study of Microsoft Employees Experiences in Remote Meetings During COVID-19 - Rintel, Sean; Wong, Priscilla; Sarkar, Advait; Sellen, Abigail (Microsoft Research, 2020)
This report explains the project data collection methodology and participation demographics for a diary study of Microsoft employees coping with all-remote meetings during the COVID-19 pandemic from April through August 2020. ACM Reference Format: Sean Rintel, Priscilla Wong, Advait Sarkar, and Abigail Sellen. 2020. Methodology and Participation for 2020 Diary Study of Microsoft Employees Experiences in Remote Meetings During COVID-19. Technical Report 2020-10-FOW-SIM1. Microsoft Research.